How does the school built environment impact students' bullying behaviour? A scoping review. (December 2022) - Francis, Jacinta; Strobel, Natalie; Trapp, Gina; Pearce, Natasha; Vaz, Sharmila; Christian, Hayley; Runions, Kevin; Martin, Karen; Cross, Donna
Abstract: Rationale: School bullying is a public health concern affecting the physical and mental health of children and young people. While school-based interventions to prevent bullying have been developed internationally, the effectiveness of many interventions has been mixed and modest. Despite a growing recognition that the school built environment may impact bullying behaviour, few anti-bullying interventions have addressed the built environment. Objective: This systematic scoping review explored existing literature for evidence that the school built environment influences bullying behaviour in school students. Methods: The review was guided by Arksey and O'Malley's methodological framework for scoping reviews. A search of six databases (Medline, PsycINFO, ERIC, EMBASE, CINAHL Plus and The Cochrane Library) identified studies addressing primary, middle and secondary school students, bullying, school bullying locations, and school built environments. Peer-reviewed journal articles published in English prior to July 19, 2021, were included. Results: In total, 7568 documents were screened by title and abstract. Following a full-text review, 61 studies (63 articles) were selected; 43 studies identified school bullying locations, and 19 studies linked features of the school built environment to bullying behaviour. Classrooms, playgrounds, and corridors were identified as common bullying locations. Features of the school built environment linked to bullying behaviour included security cameras, architectural design, aesthetics, seating, and vandalism. Conclusions: This review identified key school settings for anti-bullying interventions and identified gaps in existing built environment and bullying literature. Further analyses of published studies will inform anti-bullying policy and practice. Highlights: Scoping review of school built environment and bullying. Most published studies identified school bullying locations. Frequent bullying locations included classrooms, playgrounds and corridors. Few studies explored associations between built environments and bullying. Many research gaps exist.